DIELECTRIC STRENGTH OF SOME BLENDED POLYMERS PREPARED IN THE FORM OF THICK FILM (Biological Sciences - PJSIR, 2001)
Careful measurements of dielectric strength (DS) of blended polymeric material have been accomplished. For the measurements of DS of the films (1.0 mm thickness) prepared from these blends, McKeowns electrode system with stainless steel electrodes of 25mm diameter was used. Three types of blends were prepared. They were PE-PMA, PS-PI and PS-PE-PI. The film prepared from the blend 100% PMA had IBDS value as 200 kVmrn" whereas the additions ofPE enhanced IBDS value to 212 and 205 kVmm-1 respectively at (pEIPMA) 20/80 and 5/95 ratios. 100% PI produced IBDS as 250 k Vmrn". The addition ofPS decreased the value ofIBDS. On the other hand the blend of these polymers (PS-PE- PI) at PSIPEIPI ratio of 70110/20 gave highest IBDS (263 k'Vmm'"). The break down is initiated by free electrons accel- erated by electric field in the largest of the holes present in the amorphous phase of these polymers. These holes were formed during the production of films. Nature, ageing, photodegradation of polymeric material, shape of specimen and good contact of speciman with the surface of electrode influence on the IBDS values and help in excluding the partial discharges.